2019
DOI: 10.1002/app.48023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly(2‐ethyl‐2‐oxazoline) and UV irradiation on the melt rheology and mechanical properties of poly(lactic acid)

Abstract: To improve the suitability of poly(lactic acid) (PLA) for implantable devices, it ideally needs greater ductility without losses in strength. Here biodegradable poly(2‐ethyl‐2‐oxazoline) (PEtOx) was selected as an additive to improve hydrophilicity of PLA as well as mechanical properties, while UV irradiation was considered as a bulk modification method to increase the long‐term stability. The PLA blend showed improved tensile strength and elongation‐at‐break with small amounts of PEtOx added (1.5 wt %). Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The results found that the interaction of silicon filler in the PLA matrix has a good load-carrying ability, and the PLA with 7% silicon biocomposite has the highest Shore D hardness, attributable to the silicon filler’s load-bearing capacity. Some researchers improve polymer via UV curing or irradiation process, which was considered as a method to increase the long-term stability of polymer [ 28 ]. Lyu et al [ 15 ] added phosphine oxide (XBPO) in the PLA matrix, the results found that the maximum tensile strength of 3D printing specimens increased by 82.5% after UV process.…”
Section: Introductionmentioning
confidence: 99%
“…The results found that the interaction of silicon filler in the PLA matrix has a good load-carrying ability, and the PLA with 7% silicon biocomposite has the highest Shore D hardness, attributable to the silicon filler’s load-bearing capacity. Some researchers improve polymer via UV curing or irradiation process, which was considered as a method to increase the long-term stability of polymer [ 28 ]. Lyu et al [ 15 ] added phosphine oxide (XBPO) in the PLA matrix, the results found that the maximum tensile strength of 3D printing specimens increased by 82.5% after UV process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, post-curing technologies have been developed to perform a secondary curing of the molded material through UV light wavelength irradiation to reduce the unevenness between layers and improve the final mechanical properties. This process is however cumbersome and time-consuming [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism and structure of photo-crosslinking of PLA and its model compounds have been reported in the literature. [26][27][28] At the same time, a photo-crosslinking processing technology of PLA and its industrial UVirradiation apparatus have been developed. The major advantages of photo-crosslinking are low cost of the equipment, low energy consumption, easy operating and maintain, high production efficiency, and excellent electronic and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been significant breakthrough in the photo‐initiated crosslinking of bulk PLA. The mechanism and structure of photo‐crosslinking of PLA and its model compounds have been reported in the literature 26–28 . At the same time, a photo‐crosslinking processing technology of PLA and its industrial UV‐irradiation apparatus have been developed.…”
Section: Introductionmentioning
confidence: 99%